Growth performance, carcass and meat quality of lambs supplemented with increasing levels of a tanniferous bush (Cistus ladanifer L.) and vegetable oils. - Francisco, A; Dentinho, M T; Alves, S P; Portugal, P V; Fernandes, F; Sengo, S; Jerónimo, E; Oliveira, M a; Costa, P; Sequeira, A; Bessa, R J B; Santos-Silva, J (Meat science, 2014)
The effects of dietary inclusion of Cistus ladanifer L. (CL) and a vegetable oil blend were evaluated on growth performance, carcass and meat quality of fifty four lambs that were assigned to 9 diets, corresponding to 3 levels of CL (50, 100 and 200 g/kg DM) and 3 levels of oil inclusion (0, 40 and 80 g/kg DM). Treatments had no effects on growth rate. Oil depressed dry matter intake (P = 0.017), carcass muscle (P = 0.041) and increased (P = 0.016) kidney knob channel fat. Chemical and physical meat quality traits were not affected by treatments. Off-flavour perception was higher for 8% of oil (P < 0.001). The level of 100 g/kg DM of CL inclusion improved meat stability after 7 days of storage. Supplementation with linseed and soybean oils (2:1) was a good approach to improve meat nutritional value from feedlot lambs, increasing total n-3 PUFA.
Keywords: carcass quality; Cistus ladanifer; lamb; meat quality; oil supplementation